2011
DOI: 10.1128/jvi.01690-10
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Helicase-Primase: DNA Binding and Consequent Protein Oligomerization and Primase Activation

Abstract: The heterotrimeric helicase-primase complex of herpes simplex virus type I (HSV-1), consisting of UL5, UL8, and UL52, possesses 5 to 3 helicase, single-stranded DNA (ssDNA)-dependent ATPase, primase, and DNA binding activities. In this study we confirm that the UL5-UL8-UL52 complex has higher affinity for forked DNA than for ssDNA and fails to bind to fully annealed double-stranded DNA substrates. In addition, we show that a single-stranded overhang of greater than 6 nucleotides is required for efficient enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…In this respect it might parallel the gene 59 protein in the T4 system which acts as a helicase loader and then remains bound at moving forks as seen in the EM using nanoscale tags (41). It has previously been shown that UL5/UL8/UL52 binds preferentially to the oligo-based fork-like structures (42). Whether this binding is dictated by UL8 is to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect it might parallel the gene 59 protein in the T4 system which acts as a helicase loader and then remains bound at moving forks as seen in the EM using nanoscale tags (41). It has previously been shown that UL5/UL8/UL52 binds preferentially to the oligo-based fork-like structures (42). Whether this binding is dictated by UL8 is to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotides (42,55,69, 82 and 90 nt) described in Table 1 were used in the binding assays. M13mp18 (7249 nt) and ΦX174 (5386 nt) circular ssDNAs were from New England Biolabs.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this, the HSV H/P behaves as a single heterotrimer by gel filtration [80]. However, in the presence of forked DNA and AMP–PNP or ATP, higher-order complexes can form [96]. Furthermore, two or more H/P heterotrimers are needed in order to observe efficient primase activity [96].…”
Section: Hsv H/pmentioning
confidence: 94%
“…However, in the presence of forked DNA and AMP–PNP or ATP, higher-order complexes can form [96]. Furthermore, two or more H/P heterotrimers are needed in order to observe efficient primase activity [96]. In these experiments, primase exhibited a cooperative dependence on protein concentration while helicase activity did not.…”
Section: Hsv H/pmentioning
confidence: 99%
“…This template was initially developed to study T7 replication (4) and was re-engineered by Falkenberg et al (12) to examine HSV-1 replication. The 70-base-long minicircle they employed was a partial dsDNA circle with a 40-base ss 5Ј-tail required for efficient UL5/UL8/UL52 binding and unwinding (13) and a 20-base leading strand gap at the fork, providing a site for assembly of the replisome. They observed leading strands up to 10,000 nt and Okazaki fragments of ϳ3,000 nt in length.…”
mentioning
confidence: 99%